Factors influencing final rendering in areola tattoo reconstruction: a statistical analysis - Lusetti, Irene Laura; Marra, Caterina; Pacchioni, Lucrezia; De Santis, Giorgio (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Reconstruction of the nipple-areola complex announces the end of breast reconstruction process, sometimes difficult to live for the patient, and significantly improves the perception of body image. In literature there are no studies addressing the possible influencing factors of the final rendering of areola reconstruction with tattoo. The aim of the present study was to evaluate all the factors which could influence the yield and the final result of the nipple areola complex pigmentation. Methods: 97 patients who underwent areolar tattooing between January 2018 and February 2020 were retrospectively reviewed. Breast reconstruction timing and personal history, as well as surgical details were recorded. Results: Mean age was 52 years old (range 29-71), almost the totality of cases was women including even 2 men (one with Poland syndrome and one post mastectomy). 27 patients needed bilateral tattooing. 22 had history of adjuvant radiotherapy, 16 received neoadjuvant chemotherapy and 4 adjuvant chemotherapy. In the logistic regression analysis, radiotherapy resulted a risk factor for retattooing (p<0.05) while the autologous breast reconstruction resulted a protective factor for retattooing. Neo - and adjuvant chemotherapy were not statistically significant. Conclusions: Tissue thickness, sex, reconstructive technique and history of radiotherapy could influence the final result in areola reconstruction with tattoo, and must be taken into account to obtain the best result, knowing when the pigmentation has to be repeated.